Diamond‐Lipid Hybrids Enhance Chemotherapeutic Tolerance and Mediate Tumor Regression. (15th April 2013) - Moore, Laura; Chow, Edward Kai‐Hua; Osawa, Eiji; Bishop, J. Michael; Ho, Dean
<x xml:space="preserve">Abstract</x> Self‐assembled nanodiamond‐lipid hybrid particles (NDLPs) harness the potent interaction between the nanodiamond (ND)‐surface and small molecules, while providing a mechanism for cell‐targeted imaging and therapy of triple negative breast cancers. Epidermal growth factor receptor‐targeted NDLPs are highly biocompatible particles that provide cell‐specific imaging, promote tumor retention of ND‐complexes, prevent epirubicin toxicities and mediate regression of triple negative breast cancers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>